Inner purity and pollution in greek religion: Volume I: Early Greek religion - Petrovic, Andrej (Oxford University Press, 2016)
Was Ancient Greek religion really 'mere ritualism'? Early Christians denounced the pagans for the disorderly plurality of their cults, and reduced Greek religion to ritual and idolatry. This work argues that there was an important place for belief in Greek rituals, examining notions of inner purity and pollution as a manifestation of such belief